The temporality in forms a study of the perception of time in poetry comics - Mantaring, Gerardo Gabriel Q. (College of Arts and Letters, University of the Philippines Diliman, 2014)
Poetry comics combines various elements from both poetry and comics into a single form, as seen in the comic Geppo. Time is a human construct, created as a way to determine the "distance" between events, makers from one significant moment to another; but time is intangible and is still subject to relativity, caused by perceptions of this experienced time. The research componenet of this paper aimed to identify key characteristics and techniques used in poetry and in comic writing that contributed, if not created, to the flow of time within the piece. In the readings found, certain elements of poetry, like rhyme and meter, were adopted due to it promoting a flow or consistency to the internal while the other elements adopted by more modern poets seem to disrupt this pace, such as the case with the caesura and enjambment, both of which cause pauses and spaces within the poem. Poetry does make use of visual cues sometimes, in the way lines are scattered across the page. this physical space is the cause of disruption in this case. In comics, the flow is almost all pictorial, as seen in paneling and in the action drawn in each panel. action moves within the panel, and from panel to panel. The gutters, or the spaces in between panels, further effect the fluidity of the action's movement. The creative component is concerned with the application and creation of an output encompassing this. All text and most of the images is by myself, with Danielle Riña providing the backgrounds for thirteen pages. The subject of the work concerns a series of dreams that take place in a recurring fictional location called "Geppo". Created is a comic forty-four pages long with a few pages of script that expand the story further, if this project were to be continued outside of the thesis.